Torque density design optimization of rotating pole piece concentric magnetic gear - Mohd Ab Halim, Mohd Firdaus; Sulaiman, Erwan; Aziz, Roziah; Raja Othman, Raja Nor Firdaus Kashfi; Ab Rahman, Azhan (Springer Verlag, 2022)
Concentric magnetic gear (CMG) can achieve a torque density of more than 150 kN m/m3 through several modifcations of the original structure and the removal of material volume. However, the complexity of such a system may be impractical to assemble and realize. CMG with an alternative condition where the pole piece acts as the outer rotor can deliver higher torque instead of outer pole pair on the same structure. This unconventional condition was known since CMG inception, but it inherits the problem similar to the reluctance machine of high torque ripple. In this paper, a considerably high torque density rotating pole piece magnetic gear is proposed. Several pole pair combinations were evaluated that could yield the highest torque density at lower torque ripple. The best pole pair combination was then optimized through the width reduction of three elements, namely the pole piece, the inner yoke and the outer yoke. By enhancing the structure with the best pole pair combination, the highest torque density achieved was 364.5 kNm/m3. At the same time, the torque ripple was ably kept at below 15%. Unlike other complex structures that yield high torque density, the proposed structure is simpler, easier to assemble and hence should be more cost efective to be produced.